Treatment of 2, 4-Dichlorophenoxyacetic Acid (2, 4-D) Poisoning; a Case Study - Oghabian, Z; Ghanbarzadeh, N; Sharifi, MD; Mehrpour, O (International Journal of Medical Toxicology and Forensic Medicine, 2014)
Background: 2, 4-Dichlorophenoxyacetic Acid (2, 4-D) is an herbicide in chlorophenoxy group that use as a weed killer. Acute poisoning with 2, 4-D may be fatal in large ingestion. There is no specific antidote for 2, 4-D herbicide poisoning. We report here a case of 2, 4-D toxicity with rhabdomyolysis. Case Report: In this case study we present a case of intentional consumption of 2, 4-D herbicide with main gastrointestinal complain that became toward rhabdomyolysis and liver damage during hospital course. Successful treatment with sodium bicarbonate and other conservative therapies was performed. Conclusion: In cases of 2, 4-dichlorophenoxyacetic acid poisoning, rhabdomyolysis should be in mind and an alkaline diuresis can increase herbicide elimination as well as treatment of rhabdomyolysis should be considered. <!--[if gte mso 9]> 800x600 <![endif]-->